Komunikasi Pariwisata Berbasis Komunitas untuk Pengembangan Desa Wisata Budaya di Bukit Batu, Kabupaten Bengkalis - Noor Efni Salam; Yasir Yasir; Muhammad Firdaus; Rusmadi Awza; Evawani Elysa Lubis (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2024)
Bukit Batu Village, Bengkalis Regency has many attractions as a tourist destination. This research aims to explain the community-based tourism communication model in developing the Bukit Batu tourist village. This study uses a tourism communication approach with a community-based tourism (CBT) approach. The research method used is qualitative with a descriptive analysis approach. The research results show that tourism communication in the development of the Bukit Batu cultural tourism village is carried out by the tourism awareness group (Pokdarwis)/Bukit Batu Tourism Volunteers. This Tourism Awareness Group contributed to preparing many programs and implementing activities to advance the Bukit Batu cultural tourism village so that it won many awards. Pokdarwis' communication in tourism development is carried out in collaboration with local governments, companies and other communities such as: photographers and Creative Economy. And Activists of micro, small and medium enterprises (MSMEs). The tourism communication model in developing the Bukit Batu cultural tourism village is carried out by the community as the main driver, the private sector funding support, and the government as facilitator and regulator.